Evaluating green techniques for the extraction of L-citrulline from watermelon rind - Mahsa Mohseni; Seyed Mohammad Mousavi; Hossein Kiani; Yeganeh Azimi (Food Chemistry Advances, 2025)
L-Citrulline, a non-essential amino acid found abundantly in watermelon, provides potential antioxidant properties and promotes blood vessel dilation in the body. The extraction of L-Citrulline from watermelon rind is a promising approach to valorize agricultural waste, providing significant benefits to both the food and pharmaceutical industries. This paper aims to identify the most effective extraction method that minimizes the degradation of L-Citrulline from watermelon rind by employing various extraction techniques. In this study, advanced methods including ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), aqueous two-phase extraction (ATPE), ionic liquid-based microwave-assisted extraction (ILMAE), and ionic liquid-based ultrasonic-assisted extraction (ILUAE) were utilized under optimal conditions. The results were compared with conventional techniques to determine the most efficient green method for extracting L-Citrulline from watermelon rind. The findings revealed that the ATPE, ILMAE, and ILUAE methods achieved the highest extraction efficiencies for L-Citrulline, with rates of 85 %, 88 %, and 90 %, respectively. Compared to conventional methods, ILUAE demonstrated significantly greater extraction efficiency, with enhancements ranging from 30 % to 90 %, and a reduced extraction time from 25 to 15 min. Overall, the findings suggest that ILUAE is an effective, environmentally friendly, and cost-efficient method, making it the superior choice for extracting bioactive compounds from plant sources.